Does Use of Backyard Resources Explain the Abundance of Urban Wildlife? - Hansen, Christopher P.; Parsons, Arielle W.; Kays, Roland; Millspaugh, Joshua J. (Frontiers in Ecology and Evolution, 2020)
While urbanization is clearly contributing to biodiversity loss, certain wildlife assemblages can paradoxically be diverse and abundant in moderately developed areas. One hypothesis to explain this phenomenon is that abundant anthropogenic resources for wildlife (i.e. food and shelter) outweigh the costs associated with urbanization. To test this hypothesis, we used camera traps to measure mammal species richness, diversity, and relative abundance (i.e., detection rate) in 58 residential yards in Raleigh, North Carolina, focusing on six types of features that might be used as resources: animal feeding, vegetable gardens, compost piles, chicken coops, brushpiles, and water sources. We also placed cameras at random control sites within each yard and sampled forests in nearby suburban and rural areas for comparison. We fit mixed-effects Poisson models to determine whether yard features, yard-scale characteristics, or landscape-scale landcover predicted mammal relative abundance for eight species. We also tested if the relative abundance of native canid predators in yards was related to the number of prey (rodents and lagomorphs). Species richness, diversity, and relative abundance of most mammal species was higher in yards and suburban forests than in rural forests. Within a yard, purposeful feeding had the strongest effect on animal relative abundance, with eastern gray squirrels (Sciurus carolinensis) being the most common (32.3 squirrels/day at feeders; 0.55 at control sites; 0.29 in suburban forests; and 0.10 in rural forests). We observed species using (e.g., eating) most yard features, although canids were less likely than other taxa to use resources in yards. The presence of a yard feature did not strongly affect the abundance of species at the control site in the yard, suggesting the influence of these features was highly localized. The relative abundance of predators had a positive association with prey relative abundance, and predators were less common in yards with fences. These results demonstrate that there is high use of anthropogenic resources, especially supplemental feeding by urban wildlife, and this increase in prey species may then attract predators, which supports the hypothesis that use of supplemental food resources explains the abundance of urban wildlife.